Parents Collaborative Approach to Handle Slow Learners in The Inclusive Elementary Schoo - Linda Zakiah; Asep Supena; Nur Wulandari (Jurnal Ilmiah Sekolah Dasar, 2022)
Slow learners are children who have limited learning abilities, so they experience delays in mental development and adjustment so that they take longer and repeatedly to complete academic and non-academic tasks. This study aims to analyze the collaborative approach of parents for handling slow learners in inclusive elementary schools. This type of research is qualitative research. The research approach used in this research is a descriptive qualitative approach. The study's data collection techniques were participant observation, in-depth interviews, documentation studies, and combination/triangulation. The technique used to analyze the data is descriptive qualitative analysis. The research results, namely the collaboration carried out by the teacher, can be said to have succeeded in making changes to students in two aspects, namely cognitive aspects and affective aspects. The cognitive aspect is that students can understand the lesson, carry out their academic tasks, and get better learning outcomes. The affective aspect is seen from the increased self-confidence. Learning done repeatedly by teachers and parents can become a habit for slow learners. Parental collaboration is a form of responsibility towards their children. Parents have responsibility for the development of their children and hope that their children will be prosperous like other normal children.